ANALISIS HUKUM PERKAWINAN BEDA AGAMA ANGGOTA POLRI DIKAITKAN DENGAN UNDANG-UNDANG PERKAWINAN NOMOR 16 TAHUN 2019 - Any, Ani Yumarni (UIR Press, 2023)
Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage (UUP), both in the articles and the explanations as well as the implementing regulations there are no provisions that strictly regulate marriage of different religions, but if you look at the provisions of Article 2 paragraph (1) which states that marriage is valid if it is carried out according to the laws of each religion and belief. The purpose of this study is to find out and analyze the implementation of the marriage permit process within the scope of the National Police and to find out and analyze the efforts to register marriages for members of the Police who have different religions/beliefs. The results of the study show that the implementation of Law Number 16 of 2019 regarding marriage, namely the law of interfaith marriage is not permitted or prohibited because it is contrary to Law Number 16 of 2019 concerning Amendments to Law Number 1 of 1974 concerning Marriage, as well as religious law recognized in Indonesia such as Islam, Catholicism and Hinduism. Interfaith marriage is something that cannot be justified based on the Marriage Law and the Compilation of Islamic Law, with the consideration that the issuance of these regulations is to avoid the emergence of greater harm/loss (mafsadat) in addition to the good/gain (maslahat) that arise.